Renal Resistive Index Is Associated With Inactive Matrix Gla (γ‐Carboxyglutamate) Protein in an Adult Population‐Based Study. Issue 18 (17th September 2019) - Jaques, David A.; Pivin, Edward; Pruijm, Menno; Ackermann, Daniel; Guessous, Idris; Ehret, Georg; Wei, Fang‐Fei; Staessen, Jan A.; Pechère‐Bertschi, Antoinette; Vermeer, Cees; Vogt, Bruno; Burnier, Michel; et al.
Abstract : Background: Increased renal resistive index (RRI) has been associated with target organ damage as well as renal and cardiovascular outcomes. Matrix Gla (γ‐carboxyglutamate) protein (MGP) is a strong inhibitor of soft tissue calcification. Its inactive form (dephospho‐uncarboxylated MGP [dp‐ucMGP]) has been associated with vascular stiffness, cardiovascular outcomes, and mortality. In this study, we hypothesized that high levels of dp‐ucMGP were associated with increased RRI. Methods and Results: We recruited participants via a multicenter family‐based cross‐sectional study in Switzerland. Levels of dp‐ucMGP were measured in plasma by sandwich ELISA. RRI was measured by Doppler ultrasound in 3 segmental arteries in both kidneys. We used mixed regression models to assess the relationship between dp‐ucMGP and RRI. We adjusted for common determinants of RRI as well as renal function and cardiovascular risk factors. We included 1006 participants in our analyses: 526 women and 480 men. Mean values were 0.44±0.20 nmol/L for dp‐ucMGP and 64±5% for RRI. After multivariable adjustment, dp‐ucMGP was positively associated with RRI ( P =0.001). In subgroup analysis by age tertiles, this association was not significant in the youngest age group (<38 years; P =0.62), whereas it was significant in older age groups (38–55 and >55 years; P =0.016 and P <0.001, respectively). Conclusions: Levels of dp‐ucMGP are positively and independently associated with RRI after adjustment for common determinants of RRI, cardiovascular risk factors, and renal function. The stronger association among older adults is probably due, in part, to age‐related arterial stiffness. RRI thus seems to reflect the global atherosclerotic burden in a general adult population.